Mobility and Vitality Lifestyle Program (MOVE UP): A Community Health Worker Intervention for Older Adults With Obesity to Improve Weight, Health, and Physical Function. Issue 2 (18th June 2018) - Venditti, Elizabeth M; Zgibor, Janice C; Vander Bilt, Joni; Kieffer, Lori A; Boudreau, Robert M; Burke, Lora E; Glynn, Nancy W; Jakicic, John M; Smith, Kenneth J; Semler, Linda N; Rager, Judith R; Albert, Steven M; et al.
Abstract: Background and Objectives: Obesity rates in adults ≥65 years have increased more than other age groups in the last decade, elevating risk for chronic disease and poor physical function, particularly in underserved racial and ethnic minorities. Effective, sustainable lifestyle interventions are needed to help community-based older adults prevent or delay mobility disability. Design, baseline recruitment, and implementation features of the Mobility and Vitality Lifestyle Program (MOVE UP) study are reported. Research Design and Methods: MOVE UP aimed to recruit 26 intervention sites in underserved areas around Allegheny County, Pennsylvania and train a similar number of community health workers to deliver a manualized intervention to groups of approximately 12 participants in each location. We adapted a 13-month healthy aging/weight management intervention aligned with several evidence-based lifestyle modification programs. A nonrandomized, pre–post design was used to measure intervention impact on physical function performance, the primary study endpoint. Secondary outcomes included weight, self-reported physical activity and dietary changes, exercise self-efficacy, health status, health-related quality of life, and accelerometry in a subsample. Results: Of 58 community-based organizations approached, nearly half engaged with MOVE UP. Facilities included neighborhood community centers (25%), YMCAs (25%), senior service centers (20%), libraries (18%), senior living residences (6%), and churches (6%). Of 24 site-based cohorts with baseline data completed through November 2017, 21 community health workers were recruited and trained to implement the standardized intervention, and 287 participants were enrolled (mean age 68 years, 89% female, 33% African American, other, or more than one race). Discussion and Implications: The MOVE UP translational recruitment, training, and intervention approach is feasible and could be generalizable to diverse aging individuals with obesity and a variety of baseline medical conditions. Additional data regarding strategies for program sustainability considering program cost, organizational capacity, and other adaptations will inform public health dissemination efforts.